Strategic Directions for the Academy of Management: This Academy is for You! - Ven, Andrew H. Van de (Academy of Management Review, 2002)
Andrew H. Van de Ven, 2001 Presidential Address: Strategic Directions for the Academy of Management: This Academy Is for You!, The Academy of Management Review, Vol. 27, No. 2 (Apr., 2002), pp. 171-184